Stability of coral-endosymbiont associations during and after a thermal stress event in the southern Great Barrier Reef - Stat, Michael; Loh, W.; LaJeunesse, T.; Hoegh-Guldberg, O.; Carter, D. (Springer Verlag, 2009)
Shifts in the community of symbiotic dinoflagellates to those that are better suited to the prevailing environmental condition may provide reef-building corals with a rapid mechanism by which to adapt to changes in the environment. In this study, the dominant Symbiodinium in 10 coral species in the southern Great Barrier Reef was monitored over a 1-year period in 2002 that coincided with a thermal stress event. Molecular genetic profiling of Symbiodinium communities using single strand conformational polymorphism of the large subunit rDNA and denaturing gradient gel electrophoresis of the internal transcribed spacer 2 region did not detect any changes in the communities during and after this thermal-stress event. Coral colonies of seven species bleached but recovered with their original symbionts. This study suggests that the shuffling or switching of symbionts in response to thermal stress may be restricted to certain coral species and is probably not a universal feature of the coral-symbiont relationship. © Springer-Verlag 2009.